Potential Target Antigens for a Universal Vaccine in Epithelial Ovarian Cancer - Renee Vermeij; Toos Daemen; Geertruida H. de Bock; Pauline de Graeff; Ninke Leffers; Annechien Lambeck; Klaske A. ten Hoor; Harry Hollema; Ate G. J. van der Zee; Hans W. Nijman (Clinical and Developmental Immunology)
The prognosis of epithelial ovarian cancer (EOC), the primary cause of death from gynaecological malignancies, has only modestly improved over the last decades. Immunotherapeutic treatment using a cocktail of antigens has been proposed as a “universal” vaccine strategy. We determined the expression of tumor antigens in the context of MHC class I expression in 270 primary tumor samples using tissue microarray. Expression of tumor antigens p53, SP17, survivin, WT1, and NY-ESO-1 was observed in 120 (48.0%), 173 (68.9%), 208 (90.0%), 129 (56.3%), and 27 (11.0%) of 270 tumor specimens, respectively. In 93.2% of EOC, at least one of the investigated tumor antigens was (over)expressed. Expression of MHC class I was observed in 78.1% of EOC. In 3 out 4 primary tumors, (over)expression of a tumor antigen combined with MHC class I was observed. These results indicate that a multiepitope vaccine, comprising these antigens, could serve as a universal therapeutic vaccine for the vast majority of ovarian cancer patients.